Sex Discrimination Against Women in Initial Placement Decisions: A Laboratory Investigation - Taylor, M. Susan; Ilgen, Daniel R. (Academy of Management Journal, 1981)
The article focuses on a study which investigated sexual discrimination against women within selection decisions made for traditionally male positions. The authors hypothesize that female employees would be rated as more suitable for placement in less challenging jobs than in more challenging jobs. They also believe that people who work with a competent, high performing female in a typically male position would be display less of a tendency to rate an unknown female candidate as more suitable for initial placement in a low challenge position that a high challenge one than people who work with a high performing male. Results showed proved both hypotheses.